2008
DOI: 10.1242/jeb.020578
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and mobility of the head, neck and trunk in horses during overground locomotion: comparisons with humans and other primates

Abstract: SUMMARY Segmental kinematics were investigated in horses during overground locomotion and compared with published reports on humans and other primates to determine the impact of a large neck on rotational mobility (>20 deg.) and stability (≤20 deg.) of the head and trunk. Three adult horses (Equus caballus) performing walks, trots and canters were videotaped in lateral view. Data analysis included locomotor velocity, segmental positions, pitch and linear displacements and velocities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 81 publications
7
78
0
1
Order By: Relevance
“…Similar result were obtained for running monkeys [53]. For horses, a weaker head stabilization effect was reported [54].…”
Section: Head Stabilizationsupporting
confidence: 85%
“…Similar result were obtained for running monkeys [53]. For horses, a weaker head stabilization effect was reported [54].…”
Section: Head Stabilizationsupporting
confidence: 85%
“…The potentially energy-consuming effects of head movements relative to the trunk remain for the most part unexplored in large mammals, but have been shown to be significant in birds [9]. The few existing studies on head movements that accompany the quadrupedal mammalian walking gait [10][11][12][13][14], confirm that the head's kinematics are decoupled from the movements of the trunk. It was therefore proposed that the head movements compensated for fluctuations of the trunk in height and velocity, and stabilized optical and vestibular perception [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The potentially energy-consuming effects of head movements relative to the trunk remain for the most part unexplored in large mammals, but have been shown to be significant in birds [9]. The few existing studies on head movements that accompany the quadrupedal mammalian walking gait [10][11][12][13][14], confirm that the head's kinematics are decoupled from the movements …”
mentioning
confidence: 99%
“…Many early descriptions of primate cervical morphology as a whole concluded that skeletal variation was limited and that the region was thus relatively uninformative regarding functional or phylogenetic questions (e.g., Toerien, 1961; Ankel 1967 Ankel , 1970 Ankel , 1972. Notable exceptions include Slijper (1946) and Schultz (1961). Slijper's 1946 work investigated the presacral vertebral column across animals and developed several body-axis models stilled used today (e.g., Clauser, 1980;Shapiro, 1991;Dunbar et al, 2008;Stevens, 2013). Furthermore, the author recognized the positive relationship between body size and spinous process size and argued that the differences in cervical spinous process length between humans, great apes, and monkeys was related to head posture and position maintenance (see Toerien (1961) as well).…”
mentioning
confidence: 99%